Groundwater Utilization from Density-Stratified Non-Homogeneous Unconfined Aquifers - Jong, Tze Yong (2000)
This investigation concerns the establishing of theoretical framework of a numerical model which governs the selective withdrawal from a densitystratified groundwater reservoir to meet a certain desired water quality constraint. The general class of groundwater systems consists of a saturated porous medium where the denser saltwater tends to remain separated from the overlying freshwater. Pumping from such a stratified reservoir may result in deliveries of water of undesirable quality resulting from the unsteady mixing which occurs between the salt and freshwater layers. The equations which govern the flow of fluids and mass transport of the pollutant through the stratified groundwater reservoir were developed together with the initial and boundary conditions. The flow and solute equations were then solved by using SUTRA model that employs Galerkin finite element method. In order to verify the numerical model, an experimental laboratory sand model was constructed to study the selective withdrawal phenomenon. Four experimental tests with different set of values of well penetration depth and pumping rate were carried out to determine the pressure head and concentration distribution in the aquifer domain. To further verify the numerical model, comparisons were carried out between the numerical solutions of pressure head and concentration distribution and the experimental results, and they showed the maximum difference of 10% and 11% respectively. Good agreement was obtained as a result of these comparisons. Sensitivity analysis was carried out in order to study the effect of variations of dispersivity coefficients on the concentration distributions. It was found that increasing the dispersivity coefficients would enlarge the mixing zone above the saltwater-freshwater interface, thus caused the saltwater moving further upward to the pumping well. At the same time, a case study was also conducted at Sg. Langat basin to test the applicability of the model to the real field conditions. From the simulation of the test well with the data provided by the Geological Survey Department of Malaysia, it was found that the critical time period where the salinity-polluted water will be pumped towards the well is approximately 92 hour after the start of non-stop pumping with constant discharge rate of 114m3/hr.